Classical Marxism and Maoism: A comparative study. Issue 2 (June 2019) - Gregor, A. James
Abstract: The issue of the Marxist character of "Mao Zedong Thought" has never really been resolved. The present work is a comparative analysis of the classical Marxism of Karl Marx and Friedrich Engels and the ideology of Mao Zedong. The argument is made that whatever Marxism there was in Maoism was the "creatively developed Marxism" of V. I. Lenin—which allowed for socialist revolution in retrograde economic circumstances—something that had been specifically rejected by Marx and Engels. That led to the theoretical idiosyncrasies that characterized Maoism throughout its history, and ultimately resulted in the form rejected by Deng Xiaoping and post-Maoist China.